2016
DOI: 10.1002/pon.4270
|View full text |Cite
|
Sign up to set email alerts
|

“Our organs have a purpose”: body image acceptance in Latina breast cancer survivors

Abstract: Body image concerns are distressing for Latina breast cancer survivors. Accepting their altered appearance was an ongoing and complex process. Clinical implications include the need for psychoeducational programs and tailored interventions to enhance women's body image acceptance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 32 publications
2
40
0
4
Order By: Relevance
“…complex process influenced by the type of surgery and survivorship phase of women with breast cancer (Buki et al, 2016). Buki et al, (2016) found two themes regarding Latina women's experience with body image post breast cancer treatment: (a) perception of loss and reconstruction, (b) and achieving body image acceptance.…”
Section: Introductionmentioning
confidence: 99%
“…complex process influenced by the type of surgery and survivorship phase of women with breast cancer (Buki et al, 2016). Buki et al, (2016) found two themes regarding Latina women's experience with body image post breast cancer treatment: (a) perception of loss and reconstruction, (b) and achieving body image acceptance.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis of breast cancer disturbs the functioning of many, if not all, women in almost every sphere of life [4,5]. The psychological sphere is one of the most important because, apart from the ill person, also people who are the closest experience various types of negative emotions, such as fear, anger, the feeling of threat, helplessness and uncertainty [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…We did not nd similar studies that addressed this point, which limits our discussion. However, a qualitative research with Latina women with breast cancer, identi ed that the acceptance of changes in appearance is considered a central axis in body image [11]. The authors encourage the development of intervention strategies that favor the acceptance of appearance during and after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of fat, also considered a predictor of body dissatisfaction in women [40], especially for the lean body ideal [42], maintained this characteristic for the CG, in proportion to the Body Stigma, body concerns, transparency, and vulnerability. It is possible that this is due to the gradual and complex process of acceptance of changes in appearance from disease and treatment, requiring women to learn and deal with these changes [11].…”
Section: Discussionmentioning
confidence: 99%